2017
DOI: 10.1002/btpr.2452
|View full text |Cite
|
Sign up to set email alerts
|

A novel extracellular low‐temperature active phytase from Bacillus aryabhattai RS1 with potential application in plant growth

Abstract: Bacillus aryabhattai RS1 isolated from rhizosphere produced an extracellular, low temperature active phytase. The cultural conditions for enzyme production were optimized to obtain 35 U mL of activity. Purified phytase had specific activity and molecular weight of 72.97 U mg and ∼40 kDa, respectively. The enzyme was optimally active at pH 6.5 and 40°C and was highly specific to phytate. It exhibited higher catalytic activity at low temperature, retaining over 40% activity at 10°C. Phytase was more thermostable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…B. pumilus (MSB6) showed highest amylase activity with maximum zone of clearance. B. aryabhattai (MSB1) showed efficient phytate degrading activity with a maximum zone of clearance around the colony, supporting the observations made by Pal Roy et al [21]. Among Gram-negative bacterial isolates from hypersaline environment, most of the hydrolytic enzyme producers were belonged to the genus Halomonas [22].…”
Section: Discussionsupporting
confidence: 84%
“…B. pumilus (MSB6) showed highest amylase activity with maximum zone of clearance. B. aryabhattai (MSB1) showed efficient phytate degrading activity with a maximum zone of clearance around the colony, supporting the observations made by Pal Roy et al [21]. Among Gram-negative bacterial isolates from hypersaline environment, most of the hydrolytic enzyme producers were belonged to the genus Halomonas [22].…”
Section: Discussionsupporting
confidence: 84%
“…Application of Bacillus aryabhattai RS1 as seed and soil inoculants has been reported to improve the growth of chickpea seedlings with a significant increase in total plant biomass in the absence of additional inorganic phosphate in the soil. 29 In the present study, it was concluded that the inoculation time is important in the inoculation of the phytase enzyme, which is applied after being purified from the microorganism, and that the inoculation time should be at least 30 min.…”
Section: F I G U R Ementioning
confidence: 77%
“…In this study, it is estimated that the reason for the increase in the width of the plant crown is that the plant nutrition, especially the nutrient dissolution and uptake of phosphorus, is facilitated. In previous studies, [26][27][28][29] it has been reported that microorganisms that play a role in phosphorus solubility positively affect plant growth and development. The main use of phytase supplementation in soil is to reduce the frequent application of chemical phosphate fertilizers to the soil.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Besides inorganic phosphate, phytates are the prevalent storage form of organic P in plants which can be sequentially hydrolysed by microbial phytases to enhance P availability in soil and in the plants. For instance, an increased chickpeas seed germination, plant biomass and P content were observed after inoculation with phytase‐producing Bacillus aryabhattai RS1, under limiting P conditions (Roy et al, 2017). The role of phytases in a plant's internal metabolism has also been suggested besides in hydrolysing soil phytate.…”
Section: Rhizo‐microbiome: a Complete Solution For Nutrient Interdepe...mentioning
confidence: 99%